Simulation of applied principles of envelope functions for Fabry-Perot spectroscopy of plane wave for single-layer structures - Kosobutskyy, P.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The method to obtain analytical expressions for envelope functions in spectra
of normal incidence light reflection and transmission by single-layer structures is
proposed